Does Patient Education Prior to Arthroscopic Rotator Cuff Repair Decrease Narcotic Consumption? A Randomized Prospective Study. Issue 7 (21st July 2017) - Tjoumakaris, Fotios P.; Syed, Usman Ali Mohammed; Aleem, Alexander William; Wowkanech, Charles Dante; Getz, Charles; Weekes, Danielle; Pepe, Matthew D.; Tucker, Bradford S.; Abboud, Joseph A.; Austin, Luke
Objectives: In order to help combat opioid addiction, our objective is to see, through a randomized prospective study design, if patient education on proper use of narcotic medication would decrease narcotic consumption in the post-operative period after arthroscopic rotator cuff repair (ARCR). Methods: Patients undergoing primary ARCR at our institution were prospectively enrolled in a randomized fashion to receive either formal education on proper use of narcotics versus no education. The education group received instruction on the proper use of opioids, dosage, side effects, dependence, and addiction while the control group received education regarding the surgery alone. The education program consisted of a 2-minute narrated video in addition to a handout. All the subjects were blind to the randomization and true purpose of the study. Variables such as age, sex, and body mass index (BMI) were recorded. To determine risk of opioid abuse of the patient, the physician d a validated Opioid Risk Tool (ORT). Patients were given the same post-operative medication regimen. Patients filled out questionnaires at their 2- and 6- week follow up querying VAS pain score, refills, and total number of narcotic pills remaining. Standard statistical comparison was performed with t test calculations. Results: 67 patients d 6-week follow-up with 34 patients in the control group and 33 patients in the study group. There were no statistically significant differences in age, sex, BMI, ORT score, preoperative and postoperatively VAS score between the groups (Table 1). Patients who received pre-operative education on average consumed 26 pills compared to 35 in the control group (Table 1). More than 20 pills were consumed by only 48% of the study group compared to 76% in the control group (p = 0.01). Conclusion: Patient education is associated with a significant decrease in the number of patients consuming more than 20 narcotic pills in the acute post-operative period. Although the difference in average amount of narcotics consumed was not statistically significant, the increased frequency of patients in the control group that consumed a high number of narcotics was, suggesting benefit in preoperative education on narcotics. This is the first study to document that preoperative education can help reduce the number of patients consuming high levels of post-operative narcotics. Future recruitment and study analysis will help determine if this effect is long-lasting and can help reduce the incidence of drug dependence and addiction among this patient population. Table 1: Results and Significance Variable Study Group Control Group p-value Male/Female, n (%) 23 (70%)/10 (30%) 21 (62%) / 13 (38%) 0.49 Average Age (Range), years 60 (42-75) 58 (40-71) 0.29 Average BMI, kg/m^2 31.26 29.58 0.22 Average ORT score 1.75 1.32 0.55 VAS Pain Score, PreOp 5.29 6.61 0.12 VAS Pain Score, PostOp 2.53 3.17 0.17 Average Total Consumption 26 35 0.12